2021
DOI: 10.1111/mec.15809
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness in social groups of the emerald coral goby Paragobiodon xanthosoma creates potential for weak kin selection

Abstract: Animals forming social groups that include breeders and nonbreeders present evolutionary paradoxes; why do breeders tolerate nonbreeders? And why do nonbreeders tolerate their situation? Both paradoxes are often explained with kin selection. Kin selection is, however, assumed to play little or no role in social group formation of marine organisms with dispersive larval phases. Yet, in some marine organisms, recent evidence suggests small‐scale patterns of relatedness, meaning that this assumption must always b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…We demultiplexed loci and called individual genotypes using a python script (amplicon.py, https://bitbu cket.org/corne ll_bioin forma tics/ampli con/src/maste r/) that has been employed for other microsatellite genotyping projects (Rueger et al, 2021) In brief, the script separates paired reads by locus using Cutadapt (Martin, 2011) and then merges each pair using BBMerge (Bushnell et al, 2017). Identical reads are then counted and collapsed, with the ratio of resulting counts used to call haplotypes for each locus and individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demultiplexed loci and called individual genotypes using a python script (amplicon.py, https://bitbu cket.org/corne ll_bioin forma tics/ampli con/src/maste r/) that has been employed for other microsatellite genotyping projects (Rueger et al, 2021) In brief, the script separates paired reads by locus using Cutadapt (Martin, 2011) and then merges each pair using BBMerge (Bushnell et al, 2017). Identical reads are then counted and collapsed, with the ratio of resulting counts used to call haplotypes for each locus and individual.…”
Section: Discussionmentioning
confidence: 99%
“…We demultiplexed loci and called individual genotypes using a python script (amplicon.py, https://bitbucket.org/cornell_bioinformatics/amplicon/src/master/ ) that has been employed for other microsatellite genotyping projects (Rueger et al, 2021 ) and itself represents a refinement of the earlier Perl script used by similar studies (D'Aloia et al, 2013 ; Karn et al, 2021 ; Marcy‐Quay et al, 2020 ). In brief, the script separates paired reads by locus using Cutadapt (Martin, 2011 ) and then merges each pair using BBMerge (Bushnell et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…That study suggested that non-breeders were not closely related to the breeders ). However, more recent evidence suggests that non-breeders can sometimes be related to the breeders in A. percula (e.g., rare occurrences of full-sibs, uncles/aunts, nieces/nephews; , creating the potential for weak kin selection that might favour breeders tolerating rather than evicting non-breeders as seen in other reef fishes (Rueger et al , 2021b. This weak kin selection hypothesis is yet to be rigorously tested in A. percula or any other anemonefish, but dominants might accrue a 1-2% increase in relative fitness (rY i > rY j , Inequality 14.2) tipping the balance in favour of tolerating rather than evicting subordinates.…”
Section: Indirect Genetic Benefitsmentioning
confidence: 99%
“…Thus, although the predominance of a larval stage in marine species is often seen as a barrier to the evolution of cooperative group living driven by kin selection, it might actually be an advantage in the evolution of peaceful cooperation. Furthermore, recent evidence suggests that low but positive relatedness might have a small role in explaining peaceful cooperation in P. xanthosomus (Rueger et al, 2021), which highlights the importance of measuring genetic relatedness in marine social groups for betting understanding their grouping benefits. Ultimately, the dual benefit framework may prove useful for not only testing the grouping benefits hypotheses in the few social marine species studied thus far, but also predicting which types of species might form social groups and therefore warrant further study.…”
Section: Marine So Cial G Roups and The Dual B Enefit Fr Ame Workmentioning
confidence: 99%
“…Although the evolution of sociality with indiscriminate altruism is more likely in species that have completely lost a planktonic larval phase (e.g., Synalpheus shrimps), targeted cooperative behavior could still evolve partly by kin selection in species that show low within‐group relatedness, but that can recognize, associate, and interact frequently with relatives (Buston et al, 2009). For example, in the emerald coral goby Paragobiodon xanthosoma , low but positive relatedness within groups has been suggested to explain why breeders tolerate subordinates (Rueger et al, 2021), while a combination of future selection and ecological/social constraints may explain why nonbreeders wait peacefully in a queue for breeding positions (Wong et al, 2007; Wong, 2010).…”
Section: Evidence and Mechanisms Of Kin Structurementioning
confidence: 99%